Sosialisasi dan Workshop Implementasi Model Pembelajaran RADEC Bagi Guru-Guru Pendidikan Dasar dan Menengah: Dissemination and Implementation Workshop of RADEC Learning Models for Primary and Secondary Education Teachers - Sopandi, Wahyu (Pedagogia : Jurnal Pendidikan, 2019)
This study investigated the impact of socialization and workshops about the Read- Answer-Discuss-Explain-and Create (RADEC) learning model on teacher readiness to implement it. The investigation involved 92 teachers (elementary school, middle school, and high school teachers). The research instrument was a questionnaire consisting of two parts. The first part questionnaire was given before the activity and was intended to reveal the experience of the teachers to implement currently familiar innovative learning models. The second part questionnaire was given after the activity and was intended to reveal the teachers' readiness to implement the RADEC learning model. Data were processed quantitatively and qualitatively. The research results of the first questionnaire show that teachers had not been able to implement currently familiar innovative learning models for various reasons. The research results of the second indicate that the social- ization and workshop can prepare teachers to implement the RADEC learning model. This can be seen from the majority of those who argue that (1) the syntax of the RADEC learning model is easy to remember and understand; (2) the RADEC learning model can practice 21st century skills; and (3) they are interested in researching the implementation of the RADEC learning model.